Biogeochemical drivers of Neotropical ant activity and diversity. Issue 12 (21st December 2016) - Bujan, Jelena; Wright, S. Joseph; Kaspari, Michael
Abstract: Human activities are rapidly changing biogeochemistry across the globe, yet little is known about biogeochemical impacts on higher‐level consumers. In a Panamanian rainforest, we measured the effects of chronic nitrogen, phosphorus, and potassium fertilization on ants: hyper‐abundant terrestrial arthropods and ecosystem engineers. We tested two compatible hypotheses: the nutrient limitation hypothesis—where adding a limiting nutrient increases ant activity and abundance; and the community homogenization hypothesis—where adding a limiting nutrient decreases ant diversity. Lowland tropical rainforests are expected to be phosphorus‐limited, so we predicted higher ant activity but lower diversity on phosphorus plots. In each fertilization plot, we baited trees and lianas to attract both canopy and ground nesting ants. After controlling for temperature, which accounted for roughly 20% of the variation in ant foraging activity, ant activity remained higher on phosphorus addition plots than on any other fertilization treatment. Genus level diversity was 16% lower on plots receiving phosphorus than the control, consistent with the paradox of enrichment frequently observed in plant communities. This pattern, however, did not hold for species level diversity. The community‐level response was largely driven by the most abundant genus, Azteca, which increased foraging activity and abundance across phosphorus plots. The high activity and low diversity of ants on experimental phosphorus plots point to the potentially strong influence of biogeochemistry on these ubiquitous insects with potential ramifications for the forest food web. This is, to our knowledge, the first study relating biogeochemistry of macronutrients to foraging activity, diversity, and abundance of consumers, implicating strong bottom‐up structuring of the ant community in one of the world's most diverse ecosystems.